Discourse Coverage Of Editorial Perspective: Framing Terrorism From The Case Of Al-Shabab’s 2013 Kenya Mall Siege - Lupita Wijaya (Ultimacomm: Jurnal Ilmu Komunikasi, 2015)
Indonesia as the biggest and most populated democratic Muslim country in the world is expected to engender distinct outlook pertaining media and religion. With the myriad of as democratic country supposes to evince the power of media as peace maker rather than warmonger. This study scrutinizes the editorial discourse of The Jakarta Post, the largest English language newspaper in Indonesia, concerning the terrorism issue of al-Shabab insurgent group in 2013 Westgate Kenya Mall attack. Opinion discourse, such as editorials, op-ed articles, and distinctive and authoritative voice that will speak to them directly, in the face of troubling or problematic circumstances. Where hard news purports to be more balanced and fair, opinion discourse problematizes the world by taking up the normative dimension of issues and events of Pan and Kosicki model, the study delves into conclusion that The Jakarta Post relentlessly portrays al-Shabab as Muslim’s jihad and randomly hooks Westgate siege with other church bombings by eliciting good guy vs. bad guys dichotomy and heroes vs. villains as the heart of current circulation of publicized news. The result indicates that the context of Indonesia as largest Muslim society in the world is distinctly at odds. Keywords: editorial, discourse, media, terrorism, The Jakarta Post